2019
DOI: 10.1002/jbm.b.34505
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the conversion of bone cement and borate bioactive glass composites

Abstract: Borate bioactive glass 13‐93B3 converts into an osteoconductive hydroxyapatite‐like material in a liquid medium. In this study, 13‐93B3 was incorporated into a commercial PMMA (poly(methyl methacrylate)) bone cement, and the conversion of the glass into a precipitate in solution was investigated with scanning electron microscopy, energy dispersive X‐ray spectroscopy, Fourier transform infrared (spectroscopy)—attenuated total reflection, and micro‐Raman spectroscopy. Glass particles of 5, 33, and 100 μm diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Na 2 CO 3 , K 2 CO 3 , MgCO 3 , CaCO 3 , NaH 2 PO 4 .2H 2 O, and H 3 BO 3 (Fisher Scientific, Hampton, NH) were mixed; placed in a platinum crucible; heated for 1 hr at 1100°C to form a molten material; and quenched between cold steel plates at 23°C to form glass frits. In this study, three particle sizes (5, 33, and 100 μm) were selected and prepared as described by Cole et al (). Glass sizes were confirmed using a particle size analyzer (Microtrac S3000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na 2 CO 3 , K 2 CO 3 , MgCO 3 , CaCO 3 , NaH 2 PO 4 .2H 2 O, and H 3 BO 3 (Fisher Scientific, Hampton, NH) were mixed; placed in a platinum crucible; heated for 1 hr at 1100°C to form a molten material; and quenched between cold steel plates at 23°C to form glass frits. In this study, three particle sizes (5, 33, and 100 μm) were selected and prepared as described by Cole et al (). Glass sizes were confirmed using a particle size analyzer (Microtrac S3000).…”
Section: Methodsmentioning
confidence: 99%
“…Two previous studies added silicate‐based bioactive glasses to acrylic bone cement and then tested the composite's improved bone‐binding ability and mechanical properties (Shinzato et al, ; Shinzato et al, ). Only three times have investigators reported combining a borate‐based bioactive glass with PMMA cements: one study examined the bioactivity and osseointegration in vivo (Cui et al, ), another examined the delivery of antibiotics from the composite material (Funk, Burkes, Cole, Rahaman, & McIff, ), and the third monitored the conversion of glass to hydroxyapatite‐like precipitate (Cole, Funk, Rahaman, & McIff, ). One of our previously published studies examined the formation of a hydroxyapatite‐like layer on the surface of the composite using scanning electron microscopy and Fourier transform infrared spectroscopy (Cole et al, ), but this study did not examine the important changes in mechanical properties of the composite that occur as the glass dissolves or the rate at which it dissolves.…”
Section: Introductionmentioning
confidence: 99%
“…[119] The results showed that the sample with a smaller glass particle size (5 µm) and a load of 30-40% could better form a precipitate layer mixed with magnesium, which is a HA-based material, helping to attach the bone to the bone cement. [120] Apart from PMMA, calcium sulfate cement (CSC) and calcium phosphate cement (CPC) are also widely used in minimally invasive surgery for percutaneous kyphoplasty (PKP) and percutaneous vertebroplasty (PVP) in the treatment of vertebral compression fracture (VCF). Although CSC and CPC show better biological activity than PMMA, when used alone, they degrade rapidly before achieving satisfactory therapeutic effect.…”
Section: Bg Bone Cementmentioning
confidence: 99%
“…Since 1969, when Larry L. Hench discovered 45S5 glass (also known as Bioglass ® ) with nominal composition of: 46.1 SiO 2 , 2.6 P 2 O 5 , 24.4 Na 2 O, 26.9 CaO (in mol %), glass materials have been considered very promising for biomedical applications with their outstanding ability to bond to bone and soft tissues 1,2 . For over 50 years, researchers explored variety of glass compositions, not only silicate 3,4 but also borate‐ 5,6 and phosphate 7 ‐based glasses. However, only two compositions: 45S5 (NovaMin ® , Biogran ® , Novabone ® , Perioglas ® ) 8 and S53P4 (53% SiO 2 , 4% P 2 O 5 , 23% Na 2 O, 20% CaO (in wt.…”
Section: Introductionmentioning
confidence: 99%